2010
DOI: 10.1016/j.ajhg.2010.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in DHDPSL Are Responsible For Primary Hyperoxaluria Type III

Abstract: Primary hyperoxaluria (PH) is an autosomal-recessive disorder of endogenous oxalate synthesis characterized by accumulation of calcium oxalate primarily in the kidney. Deficiencies of alanine-glyoxylate aminotransferase (AGT) or glyoxylate reductase (GRHPR) are the two known causes of the disease (PH I and II, respectively). To determine the etiology of an as yet uncharacterized type of PH, we selected a cohort of 15 non-PH I/PH II patients from eight unrelated families with calcium oxalate nephrolithiasis for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
178
1
8

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 208 publications
(196 citation statements)
references
References 16 publications
7
178
1
8
Order By: Relevance
“…1,12 In 2010, Belostotsky et al 13 identified different mutations in the HOGA1 gene (4-hydroxy-2-oxoglutarate aldolase, formerly known as DHDPSL; MIM# 613597) in some of their non-PHI/II patients causing PH type III (PHIII, MIM# 613616). HOGA1 encodes a mitochondrial protein of 327 amino acids (35 kDa).…”
Section: Introductionmentioning
confidence: 99%
“…1,12 In 2010, Belostotsky et al 13 identified different mutations in the HOGA1 gene (4-hydroxy-2-oxoglutarate aldolase, formerly known as DHDPSL; MIM# 613597) in some of their non-PHI/II patients causing PH type III (PHIII, MIM# 613616). HOGA1 encodes a mitochondrial protein of 327 amino acids (35 kDa).…”
Section: Introductionmentioning
confidence: 99%
“…Since the initial report of HOGA1 mutations causing PH3 (Belostotsky et al 2010), several cohorts of patients with persistent hyperoxaluria of unknown aetiology (also referred to as non-type I/type II PH) have been retrospectively studied, and HOGA1 mutations have been identified in~45% of these patients (Beck et al 2013;Monico et al 2011;Williams et al 2012). These findings have significant implications for the way in which patients with hyperoxaluria are investigated and also suggest possible treatments for PH3, now that the gene and enzyme involved have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis was confirmed by mutation screening of HOGA1. Three families have been previously described (Belostotsky et al 2010). The affected individuals from the fourth family are compound heterozygotes for the following mutations: c.107C>T and c.944_946delAGG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The glyoxylate can then be converted to oxalate through lactate dehydrogenase [6]. Interestingly, HOGA1 possesses an associated catalytic activity where oxaloacetate is converted to pyruvate and carbon dioxide [13].…”
Section: Abstract: Aldolase; Primary Hyperoxaluria; Ubiquitin Proteasomementioning
confidence: 99%